Degradation of nitroaromatic compounds by the UV–H₂O₂ process using polychromatic radiation sources - García Einschlag, Fernando Sebastián (2002)
The UV–H₂O₂ process, a standard advanced oxidation process (AOP) for water treatment, has been applied to the degradation of a series of nitroaromatic compounds (nitrobenzene, 1-chloro-2,4-dinitrobenzene, 2,4-dinitrophenol, 3-nitrophenol, 4-nitrophenol and 4-chloro-3,5-dinitrobenzoic acid) using polychromatic radiation sources. The optimal concentration of hydrogen peroxide ([H₂O₂]OPT) leading to the fastest degradation rate of a given substrate (S) was determined experimentally and estimated using a simplified kinetic model based on the main reactions involved in the first stages of the oxidation. We have shown that, under conditions of monochromatic irradiation, the ratio ROPT; (=; [H₂O₂]OPT/[S]₀) is given by a simple mathematical expression containing only a few parameters,; whereas, under conditions of polychromatic irradiation, ROPT is expressed by a complex mathematical equation (involving the spectral distribution of the lamp emission and the absorption spectra of H₂O₂ and the substrate). Two numerical analysis procedures are proposed for obtaining the bimolecular rate constants for the reaction of hydroxyl radicals with a substrate (kₛ) from this equation. The rate constants, kₛ, determined for the substrates investigated in this work are in agreement with the expected reactivity trend, taking into account the effects of substituents on the distribution of electron density in the aromatic ring. The methods proposed in this work offer a double advantage: i) a standard AOP may be used to evaluate the rate constants of reaction of substrates with hydroxyl radicals under polychromatic as well as under monochromatic irradiation, ii) optimal amounts; of additive may be obtained using only a few parameters as predictive tools.